An Evaluation of the Significance of Work-Related Influence Factors on Fitness and the Development of Medical and Orthopaedic Conditions in Military Executives. (27th September 2016) - Schulze, Christoph; Becker, Michael; Finze, Susanne; Holtherm, Christoph; Hinder, Jens; Lison, Andreas
Abstract : Occupational health promotion is an effective tool to improve the state of health of employees. As part of occupational health promotion in the German Bundeswehr, top-ranking military executives are offered a medical examination and training programme. Health-related data is collected as a basis for training and lifestyle counselling. This data was subjected to a retrospective evaluation in order to identify occupational risk factors and their correlation with cardiovascular resilience, trunk strength, and the development of orthopaedic and internal disorders. A total of 122 military executives (all male, age54.6 ± 4.2 years) answered a questionnaire aimed at evaluating private and occupational stress factors. The medical history was followed by a medical and orthopaedic examination involving a lactate performance test (treadmill or bicycle ergometry) and an isometric trunk strength measurement. The data obtained was then statistically evaluated. For military executives, work-related travelling and commuting involve a high risk of medical and orthopaedic conditions. Regular exercise leads to improved fitness levels. In order to prevent medical problems, military executives working long hours should regularly take part in fitness and weight training under professional instructions.